2006
DOI: 10.1158/1535-7163.mct-06-0105
|View full text |Cite
|
Sign up to set email alerts
|

5-Methoxy-1,2-dimethyl-3-[(4-nitrophenoxy)methyl]indole-4,7-dione, a mechanism-based inhibitor of NAD(P)H:quinone oxidoreductase 1, exhibits activity against human pancreatic cancer in vitro and in vivo

Abstract: The enzyme NAD(P)H:quinone oxidoreductase 1 (NQO1) has been found to be up-regulated in pancreatic cancer as well as many other solid tumors. A recent study showed that inhibition of NQO1 in pancreatic cancer cells using the nonselective inhibitor dicumarol suppressed the malignant phenotype. The authors suggested that inhibition of cell growth might result from an increase in intracellular superoxide production due to inhibition of NQO1. We have recently shown that NQO1 can directly scavenge superoxide and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 31 publications
5
40
0
Order By: Relevance
“…After reduction to the hydroquinone form by NQO1, ES936 loses the p-nitrophenol leaving group from the indole 3-position, and the iminium ion generated subsequently reacts with tyrosine residues in the active site of NQO1, resulting in the inhibition of enzymatic activity (Winski et al, 2001). ES936 and analogs were found to be active against human pancreatic cancer (Dehn et al, 2006); however, the antitumor activity of ES936 and analogs did not correlate with their ability to inhibit NQO1 Reigan et al, 2007). We corroborated this finding in the current study using three different classes of indolequinone analogs.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…After reduction to the hydroquinone form by NQO1, ES936 loses the p-nitrophenol leaving group from the indole 3-position, and the iminium ion generated subsequently reacts with tyrosine residues in the active site of NQO1, resulting in the inhibition of enzymatic activity (Winski et al, 2001). ES936 and analogs were found to be active against human pancreatic cancer (Dehn et al, 2006); however, the antitumor activity of ES936 and analogs did not correlate with their ability to inhibit NQO1 Reigan et al, 2007). We corroborated this finding in the current study using three different classes of indolequinone analogs.…”
Section: Discussionsupporting
confidence: 81%
“…We have reported previously the development of an indolequinone, 5-methoxy-1,2-dimethyl-3-[(4-nitrophenoxy)methyl]-indole-4,7-dione (ES936, 1), that exhibited potent growth inhibition effects against human pancreatic cancer cell lines (Dehn et al, 2006). The antitumor activity of ES936 was originally attributed to its role as a mechanism-based inhibitor of human NQO1 [NAD(P)H:quinone oxidoreductase 1 (DT-diaphorase; EC 1.6.99.2)] (Winski et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The compound is also effective in vivo; MIA PaCa-2 xenografts in mice grow significantly slower after treatment with 1. 19 However, in the case of 1, our studies showed that the cytotoxicity was independent of superoxide generation, and therefore raises the question of whether NQO1 inhibition is the only mechanism operating in pancreatic cancer cells.…”
Section: Introductionmentioning
confidence: 72%